TINJAUAN HUKUM PERJANJIAN KREDIT DALAM PENYELESAIAN SENGKETA (Studi Pada Kantor BRI Kanwil Makassar) - Maulida Nur Islami; Ilham Abbas; Anmad Fadil (Qawanin Jurnal Ilmu Hukum, 2020)
Research Objectives To determine the provision of credit in the housing loan agreement (KPR) at the BRI Regional Office of Makassar and to find out the Settlement of Disputes for Bad Loans in the Home Ownership Credit Agreement (KPR) through Litigation and Non-Litigation. This research is an empirical research or field research conducted in Makassar City, precisely at the Central BRI Bank Makassar the authors chose the research location with the consideration that the research location is relevant to the problem under study.The results of this study describe the mechanism for granting credit in the Home Ownership Credit Agreement (KPR) at BRI Regional Office Makassar as follows, the customer comes to the bank, the introduction of the product by the bank, the customer comes back with a file of requirements for applying for mortgage loans, interviews, BI Checking, OTS 1 (on the spot), DUP (List of Proposed Applicants), KPK (Credit Approval Commission), SP3K (Letter of Confirmation of Approval for Credit Provision), prospective debtors are waiting for the house to be purchased first, the bank will make an estimate regarding the loan amount given to prospective debtors, Signing the agreement in front of a notary (Akad), as well as litigation and non-litigation settlement processes. As a suggestion, the parties should be able to follow the rules that have been set by the bank from the beginning of the credit application until the credit is completed properly so that bad credit does not occur. This has a good impact on the parties themselves because if it is followed properly, the circulation of money will be smooth. In applying for credit, the debtor should also be self-introspective, meaning that the credit that the debtor wants to take must be in accordance with his income and expenses so that he can pay credit regularly and not be in deficit.